P-481 Characterization of the gene expression profile of breast cancer tumours in patients undergoing ovarian stimulation for fertility preservation purposes. (30th June 2022) - Soriano, M.J; Del Castillo, L.M; Subirá, J; Herrera, A; Guerrero, Á; Gavilá, J; Santaballa, A; Díaz-García, C
Abstract: Study question: Could controlled ovarian stimulation (COS) protocols with letrozole supplementation induce changes in the molecular footprints of estrogen receptor-positive (ER+) breast cancer (BC) women? Summary answer: Ovarian stimulation with letrozole and gonadotropins does not change the gene expression profile of estrogen receptor-positive (ER+) breast malignant tumours as compared to non-stimulated patients. What is known already: Fertility preservation (FP) strategies in ER+ BC patients involve modifications of the classical COS protocols to minimise the impact of estrogen levels during ovarian stimulation. The most common approaches are using the aromatase inhibitor letrozole to block the conversion of testosterone into estradiol in the granulosa cells or the use of tamoxifen to block the ER in the breast tissue. Although retrospective studies suggest that these strategies will have no impact on patient's survival and disease progression, little is known regarding the effect of the ovarian stimulation on the genomic fingerprints of the exposed cancerous tissue. Study design, size, duration: Retrospective, non-randomized, comparative study. Gene expression profiles were compared in biopsies at diagnosis and during excision surgery in two groups of ER+ BC patients: Patients undergoing COS for FP before surgery (COS group, n = 10) and patients not undergoing any type of COS (Control group, n = 11). The former received letrozole (5mg/day) supplements during COS. The latter included 7 patients not doing FP and 4 undergoing ovarian cortex cryopreservation. Patients were recruited between 2009 and 2021. Participants/materials, setting, methods: Single 5-µm sections of formalin-fixed, paraffin-embedded (FFPE) needle core biopsy (NCB) and breast surgery (BS) tumour samples were obtained prior to starting gonadotoxic therapies. Differential gene expression and gene set analysis (GSA) was performed in tumour samples before (NCB-sample) and after COS (BS-sample). Simultaneous, quantitative detection of 2549 genes associated with tumour biology was performed with the HTG EdgeSeq Oncology Biomarker Panel. Tumour cell proliferation was also assessed by Ki67 staining. Main results and the role of chance: Patients were younger in the COS group (COS: 30.2±3.4 vs Control: 34.5±2.3; p = 0.004). None of the patients experienced any relapse during the observation period. The length of COS was 11.5±3.5 days and 10.6±6.8 MII oocytes were vitrified. The exploratory analysis using principal component analysis revealed no relationships between the two BC biopsy samples and gene expression levels in the experimental groups. The differential expression analysis just revealed 6 genes significantly over-expressed after ovarian stimulation ( DUSP1, FOS, EGFR1, NR4A1, JUN and CYR61 ). From these, DUSP1, FOS, and NR4A1 were also significantly upregulated in the unstimulated group. The GSA showed the cytochrome P450 pathway was significantly enriched after COS. No pathways related to cell proliferation were differentially expressed between groups. However, in unstimulated patients, 6 KEGG pathways were upregulated, with the cytokine-cytokine receptor interaction and the Jak-STAT signalling pathway being the most enriched. Ki67 immunostaining showed no differences in cell proliferation after COS (22.8±7.2 vs 24.0±6.9, p = 0.723). The rate of cell proliferation also remained constant in unstimulated patients (22.9±8.4 vs 25.1±8.1, p = 0.560). Limitations, reasons for caution: The main limitations of the present study are the retrospective design and the associated risk of bias, although the population is very homogeneous when it comes to clinical characteristics; and the fact that molecular footprints are only interim markers of survival/response to the treatment. Wider implications of the findings: The present study provides molecular evidence supporting the safety of COS using letrozole for oocyte vitrification in young BC patients undergoing ovarian stimulation. This information is crucial to support patient guidance during discussions about fertility preservation. Trial registration number: Not applicable